Selection criteria and husbandry practices of indigenous chicken producers in Northwest Ethiopia - Muluneh, B.; Taye, M.; Dessie, Tadelle; Salilew, D.; Kebede, D.; Tenagne, A. (Elsevier, 2024)
This study was conducted to identify the selection criteria and husbandry practices of chicken producers in different agro-ecological zones of Northwest Ethiopia as input for designing a breeding program. The study employed a purposive selection of districts and peasant associations with high indigenous chicken potential. The study areas were stratified based on the major agro-ecologies (highland, midland, and lowland). A total of 360 households were included in the study, and data on chicken breeding practices, selection criteria, and reproductive performance were collected and analyzed using SPSS software. In all agro-ecologies, egg production was prioritized by chicken owners when choosing female chickens. For male chickens, plumage color (index = 0.27), appearance (index = 0.24), and growth rate (index = 0.23) were the main selection factors. Farmers kept chickens primarily to generate cash through the sale of eggs and live animals (male chickens). There was a significant difference (p < 0.01) among agro-ecologies in nutritional management and housing of chickens. Chicken flock composition showed a highly significant difference (p < 0.001) among agro-ecologies, except layers. Most of the farmers had their own cock born in the flock. Chicken owners found in all agro-ecologies were practicing culling unwanted chickens. All the reproductive performance traits have shown a highly significant (p < 0.001) difference among agro-ecologies. A relatively higher inbreeding coefficient (0.18) was obtained in the highland agro-ecology compared to midland (0.16) and lowland (0.12). The study highlighted the importance of designing breeding programs that align with farmers' production objectives and trait preferences based on specific agro-ecologies for sustainable increases in chicken productivity.